A coverage algorithm based on D-S theory for directional sensor networks. (September 2016) - Zhang, JuWei; Li, Na; Wu, Ningning; Wang, Yu; Shi, Jingzhuo
In view of the random deployment of directional sensor nodes, this article establishes the directional probability sensing model and proposes a distributed deployment strategy based on D-S theory, which makes the perceived probability of the target points in the monitoring area is equal to or greater than the threshold through the collaborative sensing among multiple nodes. The proposed algorithm uses fewer nodes to achieve the target coverage and meet the required overall coverage level. The simulation results indicate that the proposed algorithm reduces the number of nodes effectively and guarantees the better coverage.